GENEALOGI DAN TRANSFORMASI IDEOLOGI TAFSIR PESANTREN - Fadal, Kurdi (Direktorat Jenderal Bimbingan Masyarakat Islam, 2018)
This paper examines how genealogy interpretation is studied at Islamic boarding school and how the study forms the ideology in Islamic boarding school world. Based on the genealogical historical approach, this paper reveals two things. First, Islamic boarding school interpretation has genealogical traces through the intellectual Moslem scholars network in Islamic boarding school with the Moslem scholars tradition in the Middle East especially in the context of the Qur'anic interpretation study. The tradition includes teaching tradition interpretation and  writing opus tradition. Both are influenced by similar traditions in the Haramayn Land. Secondly, through the genealogical process above born its own ideology which is very influential in the Islamic boarding school world. The sufi and fiqh pattern of the Islamic boarding school interpretation is more dominant than the other patterns. The sufi patter is inseparable from the role of Islamic boarding school mufasir who also become Sufi figures. While the fiqh pattern is often encountered Islamic boarding school mufasir because fiqh is the most popular study for people in Islamic boarding school, especially the Syafi'iyah mazhab. However, as time goes by, the ideology has undergone a transformation as a adjustment form to the time needs, that is the transformation towards the specific formation Sunni ideology in the Shafi?i?s mazhab in fiqh field and al-Ghazali and Sufism field. Tulisan ini mengkaji bagaimana genealogi tafsir yang dikaji di pesantren dan bagaimana kajian tersebut membentuk ideologi pemikiran di dunia pesantren. Berdasarkan pendekatan historis-genealogis, tulisan ini mengungkapkan dua hal. Pertama, tafsir pesantren memiliki jejak genealogis melalui jaringan intelektual ulama pesantren dengan tradisi keulamaan di Timur Tengah khususnya dalam konteks kajian tafsir al-Qur?an. Tradisi tersebut meliputi tradisi mengajarkan tafsir dan tradisi penulisan karya tafsir. Keduanya dipengaruhi oleh tradisi serupa di Tanah Haramayn. Kedua, melalu proses genealogis di atas lahir ideologi tersendiri yang sangat berpengaruh di dunia pesantren. Corak sufistik dan fikih pada tafsir pesantren lebih dominan dari pada corak yang lain. Corak sufistik tidak lepas dari peran para mufasir pesantren yang sekaligus menjadi tokoh sufi. Sementara corak fikih sering dijumpai para mufasir pesantren karena fikih merupakan kajian yang paling populer bagi masyarakat di lingkungan pesantren, terutama mazhab Syafi'iyah. Namun demikian, seiring perkembangan zaman, ideologi tersebut telah mengalami transformasi sebagai bentuk penyesuaian terhadap kebutuhan zaman, yakni transformasi menuju pembentukan ideologi sunni yang spesifik pada mazhab Syafi?i dalam bidang fikih dan al-Ghazali dan bidang tasawuf.